Marginal bone loss around platform-switched and non-platform switched implants after two years of placement: a clinical trial - Ali Zarandi; Maryam Novin (Tabriz University of Medical Sciences, 2017)
Background. The present study was conducted to investigate the marginal bone loss around two different types of implant‒abutment junctions, called platform-switched (Implantium system) and non-platform switched (XiVE system) after two years of loading. Methods. Sixty-four implants in 49 patients were included in the study. The implants were placed in the posterior mandibular region according to the relevant protocols. The extent of bone loss around the implants was measured and compared after 24 months, using digital parallel periapical radiographs. Results. The means ± SE of bone loss values in the platform-switched and non-platform-switched groups were 0.47 ± 0.048 mm and 1.87 ± 0.124 mm, respectively. The difference between the two groups was statistically significant (P < 0.0001). Conclusion. The platform-switching technique seems to reduce the periimplant crestal bone resorption, which supports the long-term predictability of implant therapy.